Does opening a stock exchange increase economic growth? - Scott Baier; Jr. Gerald P. Dwyer; Robert Tamura (Federal Reserve Bank of Atlanta, 2003)
We examine the connection between the creation of stock exchanges and economic growth with a new set of data on economic growth that spans a longer time period than generally available. We find that economic growth increases relative to the rest of the world after a stock exchange opens. Our evidence indicates that increased growth of productivity is the primary way that a stock exchange increases the growth rate of output, rather than an increase in the growth rate of physical capital. We also find that financial deepening is rapid before the creation of a stock exchange and slower subsequently.
Keywords: 330